The potentials of Perna viridis shells as biomonitoring tools for cadmium contamination in coastal area of Peninsular Malaysia - Yap, C. K.; Al-Mutairi, K. A. (Corvinus University of Budapest, 2025)
This study evaluates the potential of Perna viridis shells as reliable biomonitoring materials for cadmium (Cd) contamination in coastal ecosystems across 16 sites in Peninsular Malaysia. Mussels were sampled from diverse environments, including industrial, aquaculture, and recreational areas, providing a comprehensive assessment of environmental Cd exposure. Each mussel’s shells and soft tissues were analyzed separately, with shells showing consistent, significant positive correlations with bioavailable and organic-oxidizable sediment-bound Cd fractions. These correlations were stronger in shell components, particularly in the periostracum, compared to soft tissues, suggesting that shells provide a more stable, long-term record of environmental Cd contamination. Multiple linear regression analysis further identified bioavailable Cd fractions as significant predictors of Cd accumulation in shells, indicating that shell-based monitoring can reliably reflect ambient Cd levels in sediments. Surface sediment samples were also analyzed, confirming the environmental Cd distribution across sites. Findings highlight that P. viridis shells are better than soft tissues in monitoring chronic Cd contamination, offering a durable, cost-effective solution for coastal pollution assessment. This approach aligns with the United Nations Sustainable Development Goals, by supporting sustainable marine conservation and pollution management practices.